Characterization of Outer Membrane Protein OmpU of Vibrio cholerae O1 - Nakasone, Noboru (American Society for Microbiology, 1998)
The outer membrane protein OmpU of Vibrio cholerae O1 strain 86B3 was characterized with reference to colonization of the intestine by the organism. The purified OmpU exhibited a pI of 3.6. Upon sodium dodecyl sulfate-polyacrylamide gel electrophoresis, it migrated to 38, 32, and 110 kDa when the sample was heated at 100°C for 2 min, 50°C for 15 min, and room temperature for 30 min, respectively. The purified OmpU was not hemagglutinative. Anti-OmpU serum did not agglutinate strain 86B3 or other V. cholerae organisms. OmpU adhered to the brush border of the rabbit small intestine; adhesion of the organisms to the intestine treated in advance with OmpU was not inhibited. Treating the organisms in advance with anti-OmpU Fab did not inhibit adhesion to the intestine. These results obtained in vitro suggest that OmpU is not involved in the adhesion of V. cholerae to the intestinal epithelium.